THE ROLE OF DIGITAL TOOLS IN MANAGING SPORTS EVENTS: A CASE STUDY OF THE TAMIL NADU CHIEF MINISTER’S CHAMPIONSHIP 2024-25 - Parmar, Dinesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The increasing adoption of digital tools has transformed sports event management, enhancing efficiency, accessibility, and inclusivity. This paper evaluates the role of the SFA Sporting Services Private Limited (Game Management System-GMS) app in organizing the Tamil Nadu Chief Minister’s Championship 2024-25. By analyzing event participation data and app functionalities, the study underscores the impact of digital solutions in streamlining operations, especially for differently-abled athletes.